PENGARUH PELATIHAN AKUNTANSI SYARIAH, SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN BMT KABUPATEN KUDUS - Husnurrosyidah, Husnurrosyidah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2018)
BMT is a sharia microfinance institution that can reach all levels of society and has the potential to develop into a professional, healthy, and sharia Islamic microfinance institution. However, based on observations in several BMTs domiciled in Kudus, Pati, Jepara and Rembang areas, it still seems that employee performance is poorly demonstrated by marketing that cannot reach the targets set by BMT, even many fictitious sales agents are very detrimental to BMT. This is due to the low internal control in the BMT. In addition, there are still many BMT employees who are professional with accounting so employees need sharia accounting training. This research is a field research with a quantitative approach. The data used are primary and secondary data with survey methods through questionnaires. There are three independent variables in this study, namely (X1) training in Islamic accounting, (X2) accounting information systems, and (X3) internal control. The dependent variable (Y) in this study is employee performance. A sample of 94 respondents, using the purposive sampling method. The results of this study indicate that: 1) sharia accounting training has an effect on employee performance indicated that the PAS direct effect coefficient on KK (path c) in model (1) is 0.12 and significant (<0.02); 2) accounting information system influences employee performance by 0.19; 3) internal control has an effect on employee performance indicated by direct effect coefficient of 0.35.